2023
DOI: 10.1021/acs.analchem.3c01211
|View full text |Cite
|
Sign up to set email alerts
|

Wooden Tongue Depressor Multiplex Saliva Biosensor Fabricated via Diode Laser Engraving

Abstract: Since wood is a renewable, biodegradable naturally occurring material, the development of conductive patterns on wood substrates is a new and innovative chapter in sustainable electronics and sensors. Herein, we describe the first wooden (bio)sensing device fabricated via diode laser-induced graphitization. For this purpose, a wooden tongue depressor (WTD) is laser-treated and converted to an electrochemical multiplex biosensing device for oral fluid analysis. A low-cost laser engraver, equipped with a low-pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A total of 2384 studies were identified from the Web of Science search strategy, of which 7 [15][16][17][18][19][20][21] were deemed relevant after reviewing the title, abstract, and full text. A total of four additional articles were included from hand and citation searching [22][23][24][25]. The full search strategy results can be seen in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 2384 studies were identified from the Web of Science search strategy, of which 7 [15][16][17][18][19][20][21] were deemed relevant after reviewing the title, abstract, and full text. A total of four additional articles were included from hand and citation searching [22][23][24][25]. The full search strategy results can be seen in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to this being a viable utilisation option for routine biosensor use, the impact of eating and drinking on the biosensor sensitivity and longevity must be assessed. Two studies [21,22] had dual purposes by incorporating two biomarker detections within one sensor, which highlights a future opportunity for tailored biosensors dependent on patient-specific health needs. In this review, intraoral biosensors rely upon indwelling electronics in the oral cavity [18,20,26] or short-term contact between external active circuits and saliva-contacting electrodes [15][16][17][21][22][23]25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of CO 2 lasers to create electrochemical sensors is an approach that has several advantages over traditional sensor manufacturing methods. , In this process, a CO 2 laser is used to selectively remove or burn material from a substrate, creating conductive patterns and structures on the surface that can be used to create electrodes or other sensor components. , It can be used to create sensors from a wide range of materials, including metals, ceramics, and polymers, , patterning complex structures, reproducibly, over substrates. In the environmental sense, CO 2 laser pyrolysis is a dry process that does not require solvents or generate waste products. , Using fallen leaves as a substrate and carbon source for developing electrochemical sensors using laser pyrolysis represents a major step toward the development of high-performance, eco-friendly, and cost-effective sensors.…”
Section: Introductionmentioning
confidence: 99%